Clinical and Epidemiological Characterization of Chronic Adenoiditis in Children - Daniel Reyes Concepción; Margarita Gómez Martínez (Medisur)
Background: chronic adenoiditis, which causes the greater number of elective major surgeries in children, is a common disease in Cuba. Objectives to describe the clinical and epidemiological characteristics of chronic adenoiditis in children. Methods: a descriptive study with non-probability sampling was conducted in 98 children with chronic adenoiditis treated at the University Pediatric Hospital of Central Havana, between September 2009 and July 2011. The variables analyzed were age, sex, symptoms, signs and main clinical manifestations, personal medical history, family history, and major environmental and social risk factors. A survey was conducted to identify risk factors. Statistical analysis such as: the mean, relative frequency and frequency tables were performed. Results: highest morbidity was observed in children aged 1 to 9 years. The main features of the disease were nasal obstruction, dental malocclusion, mouth breathing and respiratory infection. The most common risk factors were attendance to day-care centers and exposure to cigarette smoke. Personal and family history of asthma and respiratory allergies was the most frequently found. Conclusion: chronic adenoiditis in pediatric patients is multifactorial in origin, and tends to decrease in the child population older than nine years.